2019
DOI: 10.1007/s13592-019-00710-y
|View full text |Cite
|
Sign up to set email alerts
|

Grooming behavior and gene expression of the Indiana “mite-biter” honey bee stock

Abstract: This study was conducted to evaluate the Indiana "mite-biter" honey bee stock, which has been selected for increased mutilation of Varroa destructor mites ("mite biting" behavior). A comparison between colonies of the selected stock and colonies of unselected Italian bees showed that the proportion of mutilated mites, the severity of mutilations, and winter colony survival were higher in Indiana mite-biter colonies. Additionally, the number of fallen mites and the rate of mite population growth were lower in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 28 publications
(33 reference statements)
1
35
0
Order By: Relevance
“…In Uruguay, Invernizzi et al [ 41 ] found that Africanized bees expressed more grooming than European bees ( A. m. ligustica ), both at colonial and individual levels. This behavior has already been reported as a valuable trait for the control of V. destructor [ 22 , 23 , 24 , 25 ]. However, we must be cautious when evaluating the importance of grooming behavior as resistance to V. destructor since a significant number of mites collected on the floor come from brood cells [ 74 , 75 ].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In Uruguay, Invernizzi et al [ 41 ] found that Africanized bees expressed more grooming than European bees ( A. m. ligustica ), both at colonial and individual levels. This behavior has already been reported as a valuable trait for the control of V. destructor [ 22 , 23 , 24 , 25 ]. However, we must be cautious when evaluating the importance of grooming behavior as resistance to V. destructor since a significant number of mites collected on the floor come from brood cells [ 74 , 75 ].…”
Section: Discussionmentioning
confidence: 91%
“…The selection of honey bees possessing these traits appears as a promising alternative to improve the resistance of honey bees to varroosis [ 18 , 19 ]. In this sense, progress has been made in the knowledge of genes associated with both behaviors, which would allow selection based on molecular markers [ 25 , 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent findings demonstrated a significant correlation between the expression of the gene neurexin and direct observations of grooming behavior (Hamiduzzaman et al, 2017). Furthermore, Morfin et al (2019) found a correlation between this gene and mite mutilation, which reinforces the validity of analyzing mite damage as an indirect measurement of grooming behavior until the development of robust markers for marker-assisted selection. Finally, efforts are being made to characterize the productivity of the selected stock under standard beekeeping management.…”
Section: Discussionmentioning
confidence: 60%
“…This widespread monitoring may help to identify numerous loci with a direct impact on the resistance of colonies of western honey bee against the Varroa mite. Many loci linked to diverse resistance traits have already been identified (Arechavaleta-Velasco et al, 2012;Behrens et al, 2011;Broeckx et al, 2019;Guarna et al, 2017;Hamiduzzaman et al, 2017;Harpur et al, 2019;Hu et al, 2016;Jiang et al, 2016;Lapidge et al, 2002;Morfin et al, 2019a;Oxley et al, 2010;Spötter et al, 2016;Spötter et al, 2012;Tsuruda et al, 2012;Zakar et al, 2014). Even though each of these studies mentions the possibility of using marker-assisted or genomic selection in honey bee breeding, to the best of our knowledge, the identified sequences have not been routinely implemented in selection programmes.…”
Section: Integrating Genomic Datamentioning
confidence: 99%